Cartografia social do mar do Ceará: perspectivas da pesca artesanal e os potenciais conflitos com a energia eólica offshore - Silva, Regina Balbino da (2024)
The diversity of coastal and marine ecosystems in Brazil is crucial for the provision of environmental, cultural and economic services to coastal communities. In the state of Ceará, the analysis of coastal zones reveals a multifaceted territory, shaped by na-tural processes and humanactions. This study focuses on the territorialization of indigenous communities, quilombolasand artisanal fishermen, highlighting the importance of artisanal fishing for community management of fishing resources. Social cartography was used as a participatory methodology to map the complexity of coastal systems, identifying shellfish gathering areas, mooring sites, fishing corrals and fishing areas, and highlighting the symbiosis between land and sea in the construction of community territories. The Ceará continental shelf, covering approximately 39,620 km², plays a significant economic role through artisanal fishing, which is essential for the local economy and environmental sustainability. In this way, the research aimed to explore marine territorialization and the impacts of the installation of Offshore Wind Farms (OWFs) on artisanal fishing in Ceará. It considers the importance of traditional fishing practices and the need for public policies that promote the sustainability of coastal communities and the conservation of marine ecosystems. The study is justified by the need to understand the potential conflicts and threats faced by fishing communities due to the expansion of offshore wind energy and other environmental and socio-economic factors. An integrated methodological approach was adopted, combining spatial and qualitative analysis with social cartography and participa tory techniques. Data collection involved 732 people, including 510 fishermen, in 37 workshops. The methodology included analyzing the impacts of PEOs on fishing activities, with a focus on the short, medium and long-distance fishing sectors, and applying the principles of energy justice. The results highlight the importance of artisanal fishing for the local economy and culture, as well as the main challenges faced by fishermen, such as environmental degradation, lack of financial resources and the absence of effective public policies. The installation of PEOs and other threats, such as overfishing, directly affect fishing production and the conservation of marine ecosystems. The study also reveals opportunities for artisanal fishing, including the valorization of coastal geo-biodiversity and the development of community and ecological tourism. The research concludes that it is essential to adopt an interdisciplinary and participatory approach to understanding territorial dynamics and developing specific public policies. Marine Spatial Planning must integrate different uses of the marine environment in a sustainable way, ensuring the coordination of maritime activities and minimizing negative impacts on fishing communities. Valuing the identities and traditional knowledge of fishing communities is fundamental to policy-making and the efficient management of marine resources.